1998
DOI: 10.1021/je9702302
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Viscosities of (Methyl Acetate or Methanol) with (Ethanol, 1-Propanol, 2-Propanol, 1-Butanol, and 2-Butanol) at 298.15 K

Abstract: Viscosities have been measured for the binary mixtures methyl acetate + (methanol, or ethanol, or 1-propanol, or 2-propanol, or 1-butanol and 2-butanol), and methanol + (ethanol, or 1-propanol, or 2-propanol, or 1-butanol and 2-butanol) and their viscosity deviations were evaluated at 298.15 K and atmospheric pressure over the entire composition range. Several semiempirical relations have been proposed to estimate dynamic viscosity, and the results were compared with the experimental data. The UNIFAC-VISCO gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 18 publications
1
17
0
1
Order By: Relevance
“…This difference can be explained because the use of automatic apparatus reduces certain parameters such as errors in reading, measure time errors, etc. We can also observe that the literature data from Canosa et al [6] present more agreement, although there are small differences. The apparatus used by Canosa et al [6] yields results with less precision, one reason that can help explain these little differences.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…This difference can be explained because the use of automatic apparatus reduces certain parameters such as errors in reading, measure time errors, etc. We can also observe that the literature data from Canosa et al [6] present more agreement, although there are small differences. The apparatus used by Canosa et al [6] yields results with less precision, one reason that can help explain these little differences.…”
Section: Resultssupporting
confidence: 77%
“…Nevertheless, for the binary systems water (1) with methanol (2) and ethanol (2) the positive deviation decreases when the length of chain of alcohol increases. In this figure, the literature values of Canosa et al [6] and Nikam et al [7] are also shown. In figures 1 and 2, we can observe that there is a large difference between the excess properties of Nikam et al [7] and the ones presented in this work.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…et al[19], Yusa et al[48], Won et al[49], Rauf et al[22],Garcia et al [60], Canosa et al[65], Alkindi et al[73], Bhuiyan and Uddin[74], Andreatta et al[76], and Mokhtarani et al[79] performing a total of 37 data points (15% of total). Though the temperature scale corrections for the data collected are of the order of the experimental uncertainties, whenever possible all the temperatures have been converted into ITS-90 by recommended methods[81,82].…”
mentioning
confidence: 99%
“…Os parâmetros mais recentes, presentes na literatura, são resultado deste projeto de mestrado e estão disponíveis em Florido et al (2013). O modelo e os parâmetros obtidos têm sido utilizados com êxito pela comunidade científica na predição de viscosidades de diversos sistemas (Bajic et al, 2013b;Canosa et al, 1998a;Canosa et al, 1998b;Canosa et al, 2000;Gonzalez et al, 2003a;Gonzalez et al, 2003b;Gonzalez et al, 2004b;Gonzalez et al, 2005;Gonzalez et al, 2006c;Gonzalez et al, 2007b;Habibullah et al, 2011;Matos et al, 2001;Matos et al, 2002.;Rodriguez et al, 1998;Rodriguez et al, 2006;Trenzado et al, 2002;Trenzado et al, 2003;Vuksanovik et al, 2013;Yang et al, 2006). A compilação dos parâmetros existentes na literatura é apresentada em anexo na tabela A1.…”
unclassified